2009
DOI: 10.1002/hep.23181
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency ablation of hepatocellular carcinoma: Long-term results and prognostic factors in 235 Western patients with cirrhosis #

Abstract: For the treatment of small hepatocellular carcinoma (HCC), radiofrequency ablation (RFA) is in some centers considered a first-line therapeutic option. However, such a strategy is still under debate with regard to tumor and patient characteristics. In this single-center study we assessed the 5-year survival and prognosis factors in 235 consecutive patients with cirrhosis (Child-Pugh A/B: 205/30) who received RFA as first-line treatment for up to three HCC <5 cm (307 tumors; mean diameter: 29 ؎ 10 mm; 53 multin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

44
310
1
10

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 418 publications
(365 citation statements)
references
References 37 publications
44
310
1
10
Order By: Relevance
“…We fully agree with Dr. Rodriguez-Sanjùn et al 1 concerning the importance of pathological examination after radiofrequency ablation (RFA), and we recognize the importance of their work that confirms previous reports. 2 Nevertheless, we cannot endorse their comment about our article 3 which suggest that RFA is only a palliative method in terms of completeness of tumor ablation.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…We fully agree with Dr. Rodriguez-Sanjùn et al 1 concerning the importance of pathological examination after radiofrequency ablation (RFA), and we recognize the importance of their work that confirms previous reports. 2 Nevertheless, we cannot endorse their comment about our article 3 which suggest that RFA is only a palliative method in terms of completeness of tumor ablation.…”
supporting
confidence: 91%
“…
We read with interest the article by N'Kontchou et al 1 concerning hepatocellular carcinoma treatment by radiofrequency ablation (RFA). They report an excellent series with impressive results in terms of both very low major complication and tract seeding rates as well as a considerable long-term survival.
…”
mentioning
confidence: 99%
“…[5][6][7][8] One of the most effective is radiofrequency ablation (RFA), 9 which is now considered potentially curative for early-stage HCCs in patients with or without surgical prospects. 3,4,[10][11][12] Local tumor control and survival are the parameters most widely used to assess the efficacy of surgical and nonsurgical treatments for HCC. [6][7][8][9][10][11][12][13][14][15][16] Data on local control are fairly easy to interpret: disease relapse at the treated tumor site is regarded as a treatment failure.…”
mentioning
confidence: 99%
“…The complete pathologic response (cPR) was around 27% to 57% of patients after TACE and 47% to 75% after radiofrequency ablation (RFA) (31,32). Recent report demonstrated that cPR reduced the recurrence of HCC after transplant and almost reduced to below 3% (33).…”
Section: Explanted Liver Pathologymentioning
confidence: 99%